The Effectiveness of using Special Labor Clothing on the Comfort Level of Multigravida Women Giving Birth in Parturition at Sultan Thaha Saifuddin Regional Hospital, Tebo, Jambi Province 2023 - Aprilia Murita Ningsih; Roni Rowawi; Elsa Puji Mediastuti; Bellia Loranthifolia; Ida Suryani (Jurnal Multidisiplin Sahombu, 2026)
This study aims to determine the differences and analyze the effectiveness of the use of special maternity clothing on the comfort level of multigravida mothers in labor at Sultan Thaha Saifuddin Tebo Regional Hospital. This study uses a quantitative method with a "Cross Sectional" approach, researchers measure variables at one time. Respondent statistical test analysis uses the T test with a paired t-test approach. This study was conducted in June-July 2023 in the delivery room of Sultan Thaha Saifuddin Tebo Regional Hospital on multigravida mothers in labor. The sampling technique used was purposive sampling according to the inclusion and exclusion criteria with a sample size of 33 multigravida mothers. The instrument in this study was a questionnaire about maternal comfort in undergoing the labor process. Bivariate analysis in this study was conducted to determine the effectiveness of the use of special maternity clothing on the level of maternal comfort in undergoing the labor process. The results of the study showed differences after the use of special maternity clothing can increase the comfort of multigravida mothers in labor. The use of maternity clothing yielded results (sig. 0.000, meaning <0.05). This indicates that the use of maternity clothing is highly effective, as seen from the post-test score of 44.1200, which is greater than the pre-test score of 37.2100, indicating a significant difference in the level of maternal comfort during labor. Conclusion: Maternity clothing is effective in improving the comfort of multigravida mothers in labor at Sultan Thaha Saifuddin Hospital, Tebo, 2023.